Electrical, Magnetic and Morphological Properties of E-Beam Evaporated Ni Thin Films - Hasan, M. K.; Shafi, M. N. A.; Siddiquy, M. N. A.; Rahim, M. A.; Islam, M. J. (Journal of Scientific Research, 2016)
Nickel (Ni) thin films in the thickness range 50?80 nm have been prepared by electron beam evaporation method at a base pressure of 4x10-5 mbar on silicon and glass substrates. Some samples have been annealed at 573 K for 1.5 h in open air. The resistivity of Ni films on silicon substrate is higher than the resistivity of Ni films on glass substrate. The TCR of Ni films is found to be positive which indicates that the Ni samples are metallic in nature. Coercivity of Ni films increases with increasing film thickness. The coercivity of 80 nm as-deposited Ni film on glass substrate is found to be ~ 9 Oe. The rms value of the surface roughness of 150 nm as-deposited Ni film on glass substrate is ~12 nm and it becomes ~ 7 nm after annealing. On the other hand, the coercivity of 90 nm and 160 nm as-deposited Ni films on silicon substrate are 50 Oe and 85 Oe, respectively. The rms value of surface roughness of 120 nm as-deposited Ni film on Si substrate is ~ 16 nm. It becomes ~ 3 nm after annealing.